Implementation of Tri Hita Karana values in pancasila education to enhance civic engagement - Rusiana, I Gusti Putu Eva; Suastika, I Nengah; Maryati, Tuty (Universitas Tanjungpura, 2026)
This study aims to analyze the implementation of Tri Hita Karana values in Pancasila Education learning to enhance the civic engagement of twelfth-grade students at SMA Negeri 1 Tabanan. This study employed a descriptive qualitative approach involving Pancasila Education teachers and twelfth-grade students as the research subjects. Data were collected through observation, interviews, and documentation, and then analyzed through the stages of data reduction, data presentation, conclusion drawing, and verification. The findings indicate that the integration of the values of parahyangan, pawongan, and palemahan in the learning process is able to strengthen students’ religious, social, and ecological character. The implementation of these values is manifested through participatory, contextual, and experience-based learning activities, such as group discussions, value reflections, and environmental care programs. This approach has proven effective in encouraging students’ increased involvement in social activities, environmental awareness, and active participation in school life as forms of civic engagement. Although several challenges were identified, including limited instructional time, differences in students’ backgrounds, and teachers’ understanding of integrating local values, school support and the availability of learning resources serve as the main supporting factors. Overall, the implementation of Tri Hita Karana values is effective in shaping students’ attitudes and behaviors in accordance with Pancasila values.